2010
DOI: 10.1021/nn9011225
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein Antibody Functionalized Carbon Nanotube Overcomes the Multidrug Resistance of Human Leukemia Cells

Abstract: Multidrug resistance (MDR), which is related to cancer chemotherapy, tumor stem cells, and tumor metastasis, is a huge obstacle for the effective cancer therapy. One of the underlying mechanisms of MDR is the increased efflux of anticancer drugs by overexpressed P-glycoprotein (P-gp) of multidrug resistant cells. In this work, the antibody of P-gp (anti-P-gp) functionalized water-soluble single-walled carbon nanotubes (Ap-SWNTs) loaded with doxorubicin (Dox), Dox/Ap-SWNTs, were synthesized for challenging the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
151
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(153 citation statements)
references
References 61 publications
0
151
0
2
Order By: Relevance
“…Firstly 1 g raw MWCNT were treated in 120 mL concentrated HNO 3 and H 2 SO 4 (1:3, v/v) solution at 120°C in an oil bath for 30 min [34]. After dilution with water by 10-fold, the solution was filtered through a 0.45 lm filter.…”
Section: Preparation Of Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly 1 g raw MWCNT were treated in 120 mL concentrated HNO 3 and H 2 SO 4 (1:3, v/v) solution at 120°C in an oil bath for 30 min [34]. After dilution with water by 10-fold, the solution was filtered through a 0.45 lm filter.…”
Section: Preparation Of Nanocarriersmentioning
confidence: 99%
“…Previously, we have investigated the cellular uptake of oxidized CNTs [33], the detection of intracellular uptake of drug molecules carried by CNTs [4], and the targeted drug delivery of Dox to multidrug resistant leukemia cells by using antibody functionalized SWCNT as nanocarrier [34]. These studies have demonstrated the potential of CNTs to carry drugs into the cells efficiently via endocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…Of the carbon-family members, sp 2 carbon-based materials such as fullerene [4,5], carbon nanotubes [1,[6][7][8][9][10][11], carbon dots [12][13][14], and graphene [15][16][17][18], have been explored for promising applications in biomedicine, including drug delivery, gene transfection, photothermal therapy, photodynamic therapy, biosensing, and even tissue engineering [19][20][21]. For instance, the hollow space in fullerene/carbon nanotubes and large surface-to-volume ratio of graphene can be used for the encapsulation and intracellular delivery of therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Such a magnetic responsive delivery system may also be applied for delivering therapeutic nucleic acid (DNA or siRNA), antibodies, growth factors, and recombinant protein to overcome the MDR property of cancer cells. For instance, the Dox‐loaded, P‐gp antibodies (anti‐Pgp) functionalized SWNTs (Ap‐SWNTs) demonstrate high drug loading efficacy and NIR controlled drug release 116. The Ap‐SWNTs were specifically sensitive to MDR human leukemia cells (K562R) with 2.4‐fold higher cytotoxicity and caused significant cell death when against K562R with near‐infrared radiation compared to free Dox, because the P‐gp antibody functionalized SWNTs could effectively interact with P‐gp, which were ubiquitously overexpressed on the membrane surface of MDR cells.…”
Section: Inorganic Nanocarriers Overcoming Drug Resistance For Cancermentioning
confidence: 99%